1971
DOI: 10.2136/sssaj1971.03615995003500030029x
|View full text |Cite
|
Sign up to set email alerts
|

Solution Ion Activity and Plant Growth

Abstract: The relation of ion uptake to soil solution composition is discussed. Uptake of a given ion depends not only on its activity in solution, but also on the activity of other ions and the relation that exists between solution ions and exchangeable or solid‐phase ions. Methods of combining all these factors are reviewed and evaluated. A dimensionless plot, suggested by Howard and Adams, which related relative plant growth to the ratio of the ion activity to the sum of ion activities in solution, ai/Σn1ai, seems to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
10

Year Published

1973
1973
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 0 publications
0
23
0
10
Order By: Relevance
“…Many studies have demonstrated that adsorptiondesorption is the most important process affecting the behavior of heavy metals in soils, hence their bioavailability and potential toxicity (Backes et al, 1995). The toxicity and bioavailability of metals also depend on their speciation (Kasawneh, 1971). A variety of factors such as organic acids in soils can affect the metal release from soil and speciation in soil solution (Mench andMartin, 1991, Rieuwerts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that adsorptiondesorption is the most important process affecting the behavior of heavy metals in soils, hence their bioavailability and potential toxicity (Backes et al, 1995). The toxicity and bioavailability of metals also depend on their speciation (Kasawneh, 1971). A variety of factors such as organic acids in soils can affect the metal release from soil and speciation in soil solution (Mench andMartin, 1991, Rieuwerts et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is thought that metal speciation and ionic activity, rather than the total amount of a dissolved metal, determine plant metal uptake (Kasawneh, 1971). Changes in the dissolved organic carbon (DOC) concentration have a strong impact Chemosphere 50 (2003) [819][820][821][822] www.elsevier.com/locate/chemosphere on the solubility of Cu in soils, with Cu being more soluble at higher DOC levels (Camobreco et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Dual ion activity ratios is a useful expression for interactive soil-plant systems (Khasawneh 1971). Ion activity values can account for the possible formation of less bioavailable products made by ion pairing or precipitation.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Dilution problems can be alleviated using nutrient ratios (Walworth and Sumner 1987). Ion activity ratios could account for nutrient interactions in soil solution during ion uptake by plants (Khasawneh 1971). Nutrient interactions not only refer to the reactions between compounds in the soil solution, but also to cation-anion, anion-anion and cation-cation interactions during plant uptake.…”
mentioning
confidence: 99%